2023
DOI: 10.1007/s00436-023-08036-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sarcocystis spp. in synanthropic (Muridae) and wild (Cricetidae) rodents from Argentina

Judith V. Bentancourt Rossoli,
Gastón Moré,
Agustina Soto-Cabrera
et al.

Abstract: The occurrence of Sarcocystis species was investigated in synanthropic (Muridae) and wild (Cricetidae) rodents from Argentina. Nine species were captured (n = 356). Sarcocysts were detected in muscles of 8.7% (31/356) and 3.7% (4/106) of the rodents by histopathology and direct microscopy, respectively. PCRs-sequencing targeting the 18S rRNA, cox1 and ITS1 regions were performed on samples with positive histopathology. Four different 18S rRNA sequences or sequence groups with high intra-group identities (99.6-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In China, a study found that 25% of large oriental voles ( Eothenomys miletus ) were infected with Sarcocystis species [ 14 ]. Similarly, in Argentina, wild Cricetidae species exhibited a prevalence of 16.08% [ 12 ], while in Japan, 16.85% of Bedford’s red-backed voles ( Clethrionomys rufocanus bedfordiae ) were infected [ 52 ]. Moreover, research conducted in the Netherlands on M. arvalis reported seasonal variations in Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, a study found that 25% of large oriental voles ( Eothenomys miletus ) were infected with Sarcocystis species [ 14 ]. Similarly, in Argentina, wild Cricetidae species exhibited a prevalence of 16.08% [ 12 ], while in Japan, 16.85% of Bedford’s red-backed voles ( Clethrionomys rufocanus bedfordiae ) were infected [ 52 ]. Moreover, research conducted in the Netherlands on M. arvalis reported seasonal variations in Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only sequences of the 18S rRNA and 28S rRNA genes have been obtained [ 9 , 10 ]. Apart from cox1 , which was used in numerous studies [ 12 , 16 , 21 , 47 , 70 , 71 ], additional genetic markers, such as ITS1 , mitochondrial cytochrome b ( cytb ), complete ITS1 – 5.8S rRNA– ITS2 region, two apicoplast genes—RNA polymerase beta subunit ( rpoB ) and caseinolytic protease C ( clpC ) demonstrate promising prospects for improved discrimination of Sarcocystis spp. in small mammals [ 47 , 66 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this genetic region has not been commonly applied for the characterization of Sarcocystis spp. from rodents, it has shown more variability compared to cox1 [9,13,59]. In contrast, cox1 is relatively conservative considering Sarcocystis spp.…”
Section: Genetic Identification Of Sarcocystis Sp Rod3 and Sarcocysti...mentioning
confidence: 99%